AAWSome: Anonymous authentication for WiFi and some real-world scenarios - Rasool, Abdullah (Student Undergraduate Research E-journal!, 2016)
WiFi networks are a popular gateway to connect to the digital world. It is often required to authenticate before being allowed to use such networks. Currently most WiFi authentication mechanisms are identifying. This is because users authenticate with a unique identifier (username, user-id). This identifier is not always important, in most cases it is sufficient to show that a user has possession of certain attributes. In this paper we introduce an anonymous authentication scheme, based on attributes rather than identities. This results in privacy-friendly authentication for WiFi networks. It can even change the way how we connect to the digital world.